Simulasi Sistem Point Of Sale Menggunakan Radio Frequency Identification Pada Pasar Swalayan - Arif Resya Saputra (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2019)
One of the factors that affect services in supermarkets is the efficiency of the time. The efficiency of the time can be done by utilizing the technology of Radio Frequency Identification (RFID). The purpose of this research is to design a simulated point of sale system using Radio Frequency Identification to time efficiency in services at the supermarket. The results of this research is a Point of Sale system simulation by using RFID technology and has been declared eligible to use based on the results of the interviews and simulations directly involving 9 of 14 employees of the cashier at Gelael Signature Makassar.